Drosophila acid DNase is a homolog of mammalian DNase II. - Evans, C.J.; Merriam, J.R.; Aguilera, R.J. (Gene, 2002)
Mammalian DNase II enzymes and the Caenorhabditis elegans homolog NUC-1 have recently been shown to be critically important during engulfment-mediated clearance of DNA. In this report, we describe the cloning and characterization of the gene encoding Drosophila DNase II. Database queries using the C. elegans NUC-1 protein sequence identified a highly homologous open reading frame in Drosophila (CG7780) that could encode a similar enzyme. Analysis of crude protein extracts revealed that wild-type Drosophila contain a potent acid endonuclease activity with cleavage preferences similar to DNase II/NUC1, while the same activity was markedly reduced in an acid DNase hypomorphic mutant line. Furthermore, the pattern of cleavage products generated from an end-labeled substrate by hypomorphic-line extracts was significantly altered in comparison to the pattern generated by wild-type extracts. Sequence analysis of CG7780 DNA and mRNA revealed that the hypomorphic line contains a missense mutation within the coding region of this gene. Additionally, Northern analysis demonstrated that CG7780 expression is normal in the mutant line, which in combination with the lowered/altered enzymatic activity and sequencing data suggested a defect in the CG7780 protein. To conclusively determine if CG7780 encoded the Drosophila equivalent of DNase II/NUC-1, transgenic lines expressing wild-type CG7780 in the mutant background were generated and subsequently shown to complement the mutant phenotype. Our results, therefore, provide compelling evidence that the predicted gene CG7780 encodes Drosophila DNase II (dDNase II), an enzyme related in sequence and activity to mammalian DNase II. Interestingly, overexpression of CG7780 both ubiquitously and in specific tissues failed to elicit any discernable phenotype.